Pengaruh Kesadaran Wajib Pajak, Saksi Perpajakan dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi di KP2KP Kutacane Aceh Tenggara - Lukman Al Hakim; Alistraja Dison Silalahi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze how the influence of taxpayer awareness, tax witnesses and tax knowledge on individual taxpayer compliance partially or simultaneously at KP2KP Kuta Cane Aceh Tengara. The approach used in this study is an associative approach and the type used is quantitative. The population used in this study was 12,986 and the sample was 100 using the puroposive sampling technique. Observations were made from November-June 2021. The data analysis technique used in this study used Validity Test, Reliability Test, Classical Assumption Test, Hypothesis Testing (t Test and F Test) and Determinant Coefficient Test. Data processing in this study using SPSS Statistics Package (Dor The Social Sciences) Version 23. The results of this study conclude that partially taxpayer awareness has a positive and significant effect on taxpayer compliance. Tax sanctions have a positive and significant effect on taxpayer compliance. Tax knowledge has a positive and significant effect on taxpayer compliance. Simultaneously, taxpayer awareness, tax witnesses and tax knowledge on taxpayer compliance, tax sanctions and tax knowledge have a positive and significant impact on individual taxpayer compliance at KP2KP KutaCane Aceh Tenggara.